2011
DOI: 10.1007/s13337-011-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cytokine and Toll-Like Receptor Gene Expression Following Infection of Indigenous and Commercial Chickens With Infectious bursal disease virus

Abstract: A comparative study of cytokine and toll-like receptor (TLR) mRNA expression in 3 weeks old indigenous and commercial chickens infected with a very virulent strain of Infectious bursal disease virus (IBDV) was performed using a custom-made microarray chip. In uninfected indigenous chickens, the basal levels of interleukin (IL) 15 were lower and IL 16 was higher than their commercial counterparts. In the IBDV infected indigenous chickens, only IL16 gene expression was down regulated, while TLR3 expression was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…In turn, these molecules trigger an appropriate immune response to eliminate the invading pathogens [21, 22]. In birds, the TLRs 3, 7, and 21 play major roles in the induction of antiviral IFN-β during such infections [23, 24]. In our study, the transcriptional levels of TLR3/7 were significantly increased post-NDV infection, suggesting the anti-NDV roles of these molecules.…”
Section: Discussionsupporting
confidence: 51%
“…In turn, these molecules trigger an appropriate immune response to eliminate the invading pathogens [21, 22]. In birds, the TLRs 3, 7, and 21 play major roles in the induction of antiviral IFN-β during such infections [23, 24]. In our study, the transcriptional levels of TLR3/7 were significantly increased post-NDV infection, suggesting the anti-NDV roles of these molecules.…”
Section: Discussionsupporting
confidence: 51%
“…Based on previous report by Rauf et al [ 10 ], TLR3 reacted differently post-infected with different strains of IBDV where upregulation of TLR3 was recorded post-classical IBDV infection but in contrary downregulation was observed post-variant IBDV infection. Another study also indicated that response of TLR3 may play an important role in resistance of the indigenous chicken against vvIBDV infection [ 27 ]. mRNA expression levels of both MHC class I and II were upregulated, but only transiently, whereas IL-10 mRNA expression levels were unaltered from those in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggested that study of alterations in serum interleukin levels might aid understanding of the mechanism modulating interference between the two viral infections. Raj et al (2011) reported that serum levels of IL1-β, IL2, IL8, IL12, IL17, and interferon (IFN)-α and -β are significantly increased in commercial chickens infected with IBDV [19].…”
Section: Discussionmentioning
confidence: 99%